Integrative omics analysis reveals the genetic basis of fatty acid composition in Brassica napus seeds - Yuting Zhang; Yunhao Liu; Zhanxiang Zong; Liang Guo; Wenhao Shen; Hu Zhao (Genome Biology)
Abstract Background The fatty acid content represents a crucial quality trait in Brassica napus or rapeseed. Improvements in fatty acid composition markedly enhance the quality of rapeseed oil. Results Here, we perform a genome-wide association study (GWAS) to identify quantitative trait locus (QTLs) associated with fatty acid content. We identify a total of seven stable QTLs and find two loci, qFA.A08 and qFA.A09.1, subjected to strong selection pressure. By transcriptome-wide association analysis (TWAS), we characterize 3295 genes that are significantly correlated with the composition of at least one fatty acid. To elucidate the genetic underpinnings governing fatty acid composition, we then employ a combination of GWAS, TWAS, and dynamic transcriptomic analysis during seed development, along with the POCKET algorithm. We predict six candidate genes that are associated with fatty acid composition. Experimental validation reveals that four genes (BnaA09.PYRD, BnaA08.PSK1, BnaA08.SWI3, and BnaC02.LTP15) positively modulate oleic acid content while negatively impact erucic acid content. Comparative analysis of transcriptome profiles suggests that BnaA09.PYRD may influence fatty acid composition by regulating energy metabolism during seed development. Conclusions This study establishes a genetic framework for a better understanding of plant oil biosynthesis in addition to providing theoretical foundation and valuable genetic resources for enhancing fatty acid composition in rapeseed breeding.